The Combinatorial Effect of Azadirachta indica INEEM) Plant with Amikacin and Tetracycline Against Clinically Important Bacteria - Ku, Tze Sin (2017)
Emergency and rapid spread of antibiotic resistance is due to the overuse and incorrect prescription of antibiotics. Antibiotics resistance has brought negative impacts such as difficulty in treating common infections in mortality rate and prolonged suffering. Current treatments to treat disease caused by antibiotics-resistant bacteria have become increasingly limited. Therefore, alternative approaches such as the use of plant extracts and combines therapy have been studied to improve the effectiveness of treatment. Plant extracts such as Azadirachta indica (neem) has shown promising use as an antimicrobial agent because it produces various secondary metabolites such as alkaloids and flavonoids. In this study, the combinatorial effect of neem leaf extracts and antibiotics against clinically important pathogens was investigated. The checkboard assay was carried out to determine the minimum inhibitory concentration (MIC) of the neem leaf extract and amikacin as well as tetracycline. However, no MIC could be determined due to the technical error of the microplate reader. Agar well and disc diffusion assay was tetracycline. An antagonistic effect was observed when Bacillus subtilis was exposed to the neem leaf extract and amikacin as a significant reduction (p<0.05) of zone of inhibition from the neem leaf extract and amikacin showed no synergistic effect against Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pneumoniae and Pseudomonas aeruginosa as the diameter of zone of inhibition obtained was the same as that of amikacin alone. No zone of inhibition was observed with Serratia marcescens when tested with neem left extract and amikacin combination. On the other hand, synergism between neem left extract and tetracycline against Propionibacterium acnes, Bacillus subtilis and Streptococcus pneumoniae ere obtained which showed significant enlargement (p<0.0.5) oo zone of inhibition as compared to tht of tetracycline alone. The combinatorial effect of neem left extract and tetracycline alone. No zone of inhibition was observed with Pseudomonas aeruginosa and Serratia marcescens when tested with neem left extract and tetracycline combination. In conclusion, neem left extract showed a better combinatorial effect with tetracycline compared to amikacin due to the synergistic action between neem left extract and tetracycline. Antagonism between neem left extract and tetracycline. Antagonism between neem left extract and amikacin suggest that combining these agents will reduce the efficacy of amikacin